2009
DOI: 10.3989/gya.075008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of new Peanut (Arachis hypogaea L.) cultivars

Abstract: RESUMEN Composición nutricional de nuevas variedades de cacahuate (Arachis Hypogaea L.)Se estudio el rendimiento agrícola y composición quími-ca (proteína, grasa, carbohidratos, fibra y cenizas), perfil de amino ácidos, digestibilidad, perfil de ácidos grasos, contenido de tocoferol y de esteroles de seis variedades de cacahuate (Arachis hypogaea L.) Col-24-Gro, Col-61-Gto, VA-81-B, Ranferi Díaz, NC-2 y Florunner. Los resultados mostraron que el mayor rendimiento se logró en las variedades Ranferi Díaz y Col-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The CC contents of peanut varieties and lines differed statistically significantly in this study (Table 3) and ranged between 1.69% and 5.29%. Campos-Mondragón et al (2009) reported that the cellulose content of 6 different peanut varieties were between 3.0% and 4.4%; while Ibraheem, Kabeir, Mohammed and Bhagiel (2015) found it as 2.08%, and Shibli, Siddique, Raza, Ahsan and Raza (2019) between 4.95% and 8.53%. The recommended cellulose content for peanuts is 8.50% (Barbara et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CC contents of peanut varieties and lines differed statistically significantly in this study (Table 3) and ranged between 1.69% and 5.29%. Campos-Mondragón et al (2009) reported that the cellulose content of 6 different peanut varieties were between 3.0% and 4.4%; while Ibraheem, Kabeir, Mohammed and Bhagiel (2015) found it as 2.08%, and Shibli, Siddique, Raza, Ahsan and Raza (2019) between 4.95% and 8.53%. The recommended cellulose content for peanuts is 8.50% (Barbara et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Harvest time is one of the factors affecting CA; and as the harvest is delayed, the CA content increases. Campos-Mondragón et al (2009) reported that the CA values of 6 different peanut varieties ranged between 2.0 and 2.5%; while Ibraheem, Kabeir, Mohammed and Bhagiel (2015) found it as 1.13%. Mora-Escobedo, Hernández-Luna, Joaquín-Torres, Ortiz-Moreno and Robles-Ramírez (2015) found the ash content of peanut varieties between 2.22 and 2.50%, while Yadav, Edukondalu, Patel and Rao (2018) found it to be 1.84%.…”
Section: Resultsmentioning
confidence: 99%
“…The average oil content in the grains was approximately 47% (Table 9), within the average found in peanut cultivars (Campos-Mondragon et al, 2009). The higher oil contents were observed in BRS 151-L7 (48.4%), IAC Tatuí (48.2%), BRS Havana (48.1%), IAC Poitara (47.3%), IAC Oirã (47.1%) and IAC Tupã (47%).…”
Section: Resultsmentioning
confidence: 52%
“…Peanut (Arachis hypogaea L.) is grown in Brazil mainly to meet the food industry. The peanut seeds have high oil content, which makes this legume a promising feedstock for biodiesel production (Campos-Mondragon et al, 2009;Santos et al, 2012b). Processing of peanut generates numerous by-products that have various applications in the food and feed industry (Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are α-, β-, γ-, and δ-tocopherols and α-, β-, γ-, and δ-tocotrienols, collectively known as tocochromanols (Ahsan et al, 2015). The main tocopherols in peanuts were reported to be α-, γ-and δ-tocopherol with δtocopherol having the least concentration (Medina-Juá rez et al, 2009). The concentrations of α-, γ-, and δ-tocopherol in peanut oil are 8.…”
Section: Introductionmentioning
confidence: 99%